Konsep Toleransi dalam Islam dan Implementasinya di Masyarakat Indonesia - Mohammad Fuad Al Amin Mohammad Rosyidi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2019)
This article describes the concept of tolerance in Islam and its implementation in Indonesian society. This research uses descriptive qualitative method. The Indonesian community consists of different tribes, religions, and culture. The differences can be a strength, if managed correctly. But this can also be a threat of division if it is wrong to deal with it. The fact that occurs at the end of this decade, Indonesia society faced with the split between the people of nation. Violence and conflicts in the name of religion began popping up. This is due to start the loss of tolerance between believers. One of the efforts that need to be done is internalize the value of tolerance in Islam into social life. The concept of tolerance in Islam has several characteristics, including: al-hurriyah fi al-i’tiqâd (freedom of belief), al-insâniyyah (human values), and al-wasathiyyah (moderate).